The Strategy of Dormitory Sunan Ampel Al-Aly's in Increasing Spiritual Intelligence in Students - Binnuril Haqqil Ba’its Putri; Muslihun Muslihun (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Spiritual Intelligence is very important for everyone to have, especially students at the private Islamic University of Maulana Malik Ibrahim Malang Because spiritual intelligence is the highest intelligence among other intelligence. By having high spiritual intelligence, a person will become a worthy person, both in terms of his faith and Islam. Private Islamic University of Maulana Malik Ibrahim Malang Maulana Malik Ibrahim Malang has a goal, namely to provide students with spiritual depth. So private Islamic University of Maulana Malik Ibrahim Malang implements several strategies to increase the spiritual intelligence of students at the private Islamic University of Maulana Malik Ibrahim Malang. This research uses qualitative research with a descriptive approach. The object of this research was carried out at the dormitory Sunan Ampel Al-Aly private Islamic University of Maulana Malik Ibrahim Malang. Data collection techniques use observation, interviews, and documentation. Data sources in this research include murobbi, musyrif, and students. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The triangulation used to test the validity of the data is technique and source triangulation. The research results show that (1) dormitory Sunan Aampel Al-Aly's strategy for increasing spiritual intelligence in the student dormitory at the private Islamic University of Maulana Malik Ibrahim Malang consists of three stages: Emotional Clarification, Mental Development, and Personal and Social Resilience. In order to clarify emotions, dormitory Sunan Ampel Al-Aly implemented a program of ubudiyah activities: istighosah, wirdul lathif, rotibul haddad, tahlil, yasin, al-kahfi, tashih Al-Qur'an, and birthday diba'iyah. As for dormitory's mental development, Sunan Ampel Al-Aly held ta'lim afkar by studying the book qomi'ut tughyan. Furthermore, for personal and social resilience, dormitories Sunan Ampel Al-Aly held ta'lim afkar by studying the book of tadzhib. (2) The impact of Sunan Ampel Al-Aly's dormitory strategy in increasing spiritual intelligence in the students' dormitory at the private Islamic University of Maulana Malik Ibrahim Malang is: increasing spiritual awareness of students, strengthening mental and emotional resilience, improving the quality of interpersonal relationships.